2021
DOI: 10.1007/s43450-021-00167-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-arthritic Activities of Glycosylated Flavonoids from Syzygium jambos in Edematogenic Agent-Induced Paw Edema in Mice

Abstract: Two glycosylated flavonoids, the quercetin-3-O-β-d-xylofuranosyl-(1 → 2)-α-l-rhamnopyranoside and myricetin-3-O-β-d-xylofuranosyl-(1 → 2)-α-l-rhamnopyranoside, were isolated from the CH2Cl2/MeOH fraction of Syzygium jambos (L.) Alston, Myrtaceae. The structures of these compounds were elucidated by spectroscopic means. The cytotoxicity of the compounds was evaluated against the RAW 264.7 cell lines by the lactate dehydrogenase assay. All analyzed compounds were less cytotoxic than the positive control (actinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Potent antioxidant activity was also observed in the FRAP assay (Table 4). It is well established through the in vitro assays that S. jambos has substantial antioxidant potential (Ticona et al, 2021). This was also supported by the studies of Sobeh et al, who reported that the Egyptian S. jambos harbors plenty of phenolic compounds such as flavonol glycosides, flavones ellagitannins, and phenolic acids, which are known to be endowed with strong antioxidant properties (Sobeh et al, 2018a).…”
Section: In Vitro Antioxidant and Anti-aging Activitiesmentioning
confidence: 76%
“…Potent antioxidant activity was also observed in the FRAP assay (Table 4). It is well established through the in vitro assays that S. jambos has substantial antioxidant potential (Ticona et al, 2021). This was also supported by the studies of Sobeh et al, who reported that the Egyptian S. jambos harbors plenty of phenolic compounds such as flavonol glycosides, flavones ellagitannins, and phenolic acids, which are known to be endowed with strong antioxidant properties (Sobeh et al, 2018a).…”
Section: In Vitro Antioxidant and Anti-aging Activitiesmentioning
confidence: 76%
“…A variety of mediators, including cytokines (IL-1B and TNF-alpha), GM-CSF, interferons, and PGDF, are released during chronic inflammation. These mediators are responsible for pain, bone and cartilage degradation, and severe impairment [ 21 ].Standard drug and hydro-alcoholic Bombax ceiba extract, on the other hand, can significantly suppress paw swelling and decrease paw volume in both acute and chronic phases, which may be due to the suppression of inflammatory mediators released due to Freund's adjuvant induction [ 22 ]. Though the exact mechanism of inflammation suppression is unknown, it can be connected with the presence of alkaloids and flavonoids in suppressing inflammation and antioxidant activity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These phytocompounds are broadly involved in health-promoting effects and crucial components in a variety of pharmaceutical, nutraceutical, medicinal and cosmetic applications. (14) These are also associated with their anti-oxidative (40), anti-mutagenic (41), anti-inflammatory (42), and anti-carcinogenic (43) properties. Some researchers reported the tremendous scope of flavonoids as potential drugs in preventing chronic diseases and future research directions.…”
Section: Discussionmentioning
confidence: 99%